Pengaruh Corporate Environmental Performance dan Intellectual Capital terhadap Sustainability Reporting dengan Good Corporate Governance Sebagai Moderasi - Jawak, Anastasia Yolanda Putri br; Lubis, Irsad (Politeknik Negeri Ambon, 2023)
The purpose of this study is to be able to react to that given by the company's environmental performance as well as intellectual capital to sustainability reporting with good corporate governance as moderation. The data used in this study comes from secondary data. Where the companies used in this study are companies that are categorized into the mining sector, other industries, consumer goods, infrastructure, utilities and transportation industries by the Indonesia Stock Exchange (IDX) during the 2017-2019 period. Sampling in this study using purposive sampling technique so that the number of companies used in this study were 42 companies. The data that has been collected is then tested using panel data regression analysis. The results obtained are based on data processing obtained by the company's environmental performance which has a significant positive effect on sustainability reporting, while intellectual capital does not have a significant positive effect on sustainability reporting. The research variables of good corporate governance do not moderate the influence of corporate environmental performance and intellectual capital on sustainability reporting. Â